2002
DOI: 10.1038/sj.eye.6700089
|View full text |Cite
|
Sign up to set email alerts
|

Effect of religious fasting on intra-ocular pressure

Abstract: Aim The objective of this study was to find out the effect of religious fasting on intraocular pressure. Methods Intra-ocular pressure by applanation tonometer was measured four times a day in 38 healthy young adult male patients. The mean age of patients was 29 years. Body weight was measured to assess the extent of dehydration caused by fasting. Results There was a statistically significant difference between the intra-ocular pressure during fasting and the non-fasting period (P Ͻ 0.001). There was weight lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 3 publications
(2 reference statements)
4
37
0
Order By: Relevance
“…In our study, the mean IOP was 14.19±3.53 mmHg at 0800 hours and showed a decrease in the afternoon to 11.74±2.39 mmHg at 1600 hours during fasting period, whereas a 1.1 mmHg IOP rise was observed during the non-fasting period, which was nonsignificant. In the study group of Dadeya et al, 4 there was a 0.1 mmHg rise in the fasting group and 0.6 mmHg rise in the non-fasting group between 0900 and 1500 hours. They also noticed another 1.6 mmHg rise in 3 h between 1500 and 1800 hours in the non-fasting group.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our study, the mean IOP was 14.19±3.53 mmHg at 0800 hours and showed a decrease in the afternoon to 11.74±2.39 mmHg at 1600 hours during fasting period, whereas a 1.1 mmHg IOP rise was observed during the non-fasting period, which was nonsignificant. In the study group of Dadeya et al, 4 there was a 0.1 mmHg rise in the fasting group and 0.6 mmHg rise in the non-fasting group between 0900 and 1500 hours. They also noticed another 1.6 mmHg rise in 3 h between 1500 and 1800 hours in the non-fasting group.…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few reports in the literature on fasting and IOP. [3][4] Kayikcioglu et al 3 showed that fasting did not alter diurnal IOP in healthy subjects. Dadeya et al 4 measured IOP four times during the daytime beginning from 0900 to 1800 hours with 3 h interval and found significantly lower IOP values at all time points during fasting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations